2022
DOI: 10.1093/mnras/stac2549
|View full text |Cite
|
Sign up to set email alerts
|

The luminosity function of ringed galaxies

Abstract: We perform an analysis of the luminosity functions (LFs) of two types of ringed galaxies – polar-ring galaxies and collisional ring galaxies – using data from the Sloan Digital Sky Survey (SDSS). Both classes of galaxies were formed as a result of interaction with their environment and they are very rare objects. We constructed LFs of galaxies by different methods and found their approximations by the Schechter function. The luminosity functions of both types of galaxies show a systematic fall-off at low lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The occurrence rate of polar-ring galaxies in Stripe 82 was estimated using the approach described in Smirnov & Reshetnikov (2022). Initially, the completeness of the PRG and the entire Stripe 82 samples was assessed using the V/V max method (Huchra & Sargent 1973), resulting in correction factors of 2.32 and 1.41, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence rate of polar-ring galaxies in Stripe 82 was estimated using the approach described in Smirnov & Reshetnikov (2022). Initially, the completeness of the PRG and the entire Stripe 82 samples was assessed using the V/V max method (Huchra & Sargent 1973), resulting in correction factors of 2.32 and 1.41, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Reshetnikov et al (2011) estimated that 0.17% of nearby galaxies with absolute magnitudes in the range of M B = −17 to −22 mag may have polar rings; however, if projection effects are taken into account, this fraction amounts to ∼0.4%. Recently, Smirnov & Reshetnikov (2022) investigated the luminosity functions of 103 'best' candidates for PRGs selected from Whitmore et al (1990), the SPRC, and Reshetnikov & Mosenkov (2019). They concluded that only ∼0.01% of nearby galaxies with absolute magnitudes in the range M r = −17 to −22 mag have polar rings, but their frequency of occurrence increases significantly with redshift up to z ∼ 1.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of the representative catalog of galaxies with ring(s) could be very useful ( [130,131]). For example, Smirnov and Reshetnikov [131] collected the samples of polar-and collision-ring galaxies from all the published data in several deep fields.…”
Section: Notes On Problem Points Of Cnn Image-based Galaxy Classifica...mentioning
confidence: 99%
“…The creation of the representative catalog of galaxies with ring(s) could be very useful ( [130,131]). For example, Smirnov and Reshetnikov [131] collected the samples of polar-and collision-ring galaxies from all the published data in several deep fields. Doing this painstaking preliminary search, they constructed the luminosity function for the ringed galaxies and confirmed the increase in their volume density with redshift: up to z ~1 their density grows as (1 + z) m , where m  5.…”
Section: Notes On Problem Points Of Cnn Image-based Galaxy Classifica...mentioning
confidence: 99%